2019
DOI: 10.1111/jcpp.13165
|View full text |Cite
|
Sign up to set email alerts
|

Parent–child neural synchrony: a novel approach to elucidating dyadic correlates of preschool irritability

Abstract: Background: Research to date has largely conceptualized irritability in terms of intraindividual differences. However, the role of interpersonal dyadic processes has received little consideration. Nevertheless, difficulties in how parentchild dyads synchronize during interactions may be an important correlate of irritably in early childhood. Innovations in developmentally sensitive neuroimaging methods now enable the use of measures of neural synchrony to quantify synchronous responses in parent-child dyads an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
89
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 60 publications
(94 citation statements)
references
References 57 publications
5
89
0
Order By: Relevance
“…These findings plausibly suggest that mothers increase the degree of coordination between their and their infant’s affective states after distressing situations in order to help their child soothe and regulate after experiencing a stressor ( Moore & Calkins, 2004 ). Previous work from our lab suggests that higher child irritability is associated with lower parent-child neural synchrony during recovery from experimentally-induced stress, suggesting recovery processes are affected by irritability/poor anger regulation ( Quiñones-Camacho et al, 2019 ). Despite this growing literature, to our knowledge, no research has examined the interaction between adversity and experimentally-induced stress and recovery processes in the prediction of parent-child synchrony.…”
Section: Introductionmentioning
confidence: 85%
“…These findings plausibly suggest that mothers increase the degree of coordination between their and their infant’s affective states after distressing situations in order to help their child soothe and regulate after experiencing a stressor ( Moore & Calkins, 2004 ). Previous work from our lab suggests that higher child irritability is associated with lower parent-child neural synchrony during recovery from experimentally-induced stress, suggesting recovery processes are affected by irritability/poor anger regulation ( Quiñones-Camacho et al, 2019 ). Despite this growing literature, to our knowledge, no research has examined the interaction between adversity and experimentally-induced stress and recovery processes in the prediction of parent-child synchrony.…”
Section: Introductionmentioning
confidence: 85%
“…Due to the context provided by the tasks or the age of assessed children, mostly non-verbal factors associated with neural synchronization have been explored thus far. In two of the available studies, a more naturalistic interaction allowed the additional examination of interaction quality in association with neural synchrony ( Quiñones-Camacho et al. , 2019 ; Nguyen et al.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, fNIRS data suggest the presence of synchrony in the dorsolateral prefrontal and frontopolar cortices of children with their caregivers during a cooperation task, but not a competition task or either task with a stranger (Reindl et al, 2018) and regions of the prefrontal cortex showed increased synchrony in mother–son dyads when completing a task cooperatively compared to when they completed it independently (Miller et al, 2019). Infants and young children who show prefrontal and temporo-parietal synchrony with their parent (fNIRS) tend to show more behavioral synchrony, less irritability, and more problem-solving success (Nguyen et al, 2020; Quiñones-Camacho et al, 2019). These prefrontal regions have already been implicated in the negative feedback regulation of the HPA axis and autonomic reactivity (Ulrich-Lai & Herman, 2009).…”
Section: Resultsmentioning
confidence: 99%